Strategie wychowawcze św. Pawła wobec Koryntian - Guzewicz, Mieczysław (Verbum Vitae, 2012)
One of the apostolic and literary activities of St. Paul is education. Paul’s pedagogy comes from the desire to imitate Christ’s attitude, in fidelity to God and his commandments, but also from Paul’s experience with his closest disciples and followers. In his letters, Paul shows with courage his interior, often torn apart by the negative behavior of the Christians. He feels connected with the representatives of communities founded by him like a parent with his children. The Apostle feels responsibility for Christian’s formation, their spiritual state and the quality of their relationship with Jesus.